Perancangan dan Analisis Rangka Body Mobil Listrik Kompetisi Fakultas Vokasi “aurora" - Nurcahyo, Yusuf Eko; Wisnu, Wisnu Yulianto Nugroho (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
The surge in demand for electric vehicles, including electric racing cars, has marked a significant pivot towards sustainable transportation, driven by the global imperative to reduce greenhouse gas emissions and urban air pollution. This study focuses on the structural design of a Formula Automotive Engineering (FAE) vehicle frame, which plays a crucial role in vehicle performance aspects like maneuverability, stability, and safety. With the objective of designing an efficient, lightweight, yet robust frame, this research utilizes Ansys, a leading finite element analysis software, to simulate structural static behavior and validate the frame design without the need for costly and time-consuming physical prototypes. Various simulations, including Torsion Test, Cornering Test, Aero+Cornering Test, and Frontal Impact Test, were conducted to assess the frame's response to different operational stress conditions. The results indicate that the frame withstands the imposed stresses while maintaining the necessary balance between strength and flexibility required for high-speed maneuvers and safety. This study concludes that, with advancements in engineering software, the iterative design process of electric vehicle frames can be significantly optimized, contributing to the development of competitive yet sustainable automotive technologies. Keywords: Electric Vehicles, Structural Design, Finite Element Analysis, Ansys, Stress Simulation, Sustainable Transportation